2009
DOI: 10.1111/j.1748-0361.2009.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Coverage by Primary Care Physicians in a Rural Practice‐Based Research Network: Incentives, Confidence, and Training

Abstract: Almost two fifths of surveyed primary care physicians in a rural practice-based research network provide ED coverage. Based on these physicians' low levels of confidence and desire for additional training in pediatric emergencies, effective education models are needed for physicians covering the ED at their rural hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…For populations of 15 000–25 000, there is usually a specialist surgeon supported by one or more GPS (‘mixed’ model). Lew et al [ 80 ] USA 2009 Quantitative study—survey • In rural areas EDs are often staffed by primary care physicians, rather than emergency medicine trained specialists. • More than one third of the respondent physicians currently covering the ED reported that they derive greater than 40% of their income from working in it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For populations of 15 000–25 000, there is usually a specialist surgeon supported by one or more GPS (‘mixed’ model). Lew et al [ 80 ] USA 2009 Quantitative study—survey • In rural areas EDs are often staffed by primary care physicians, rather than emergency medicine trained specialists. • More than one third of the respondent physicians currently covering the ED reported that they derive greater than 40% of their income from working in it.…”
Section: Resultsmentioning
confidence: 99%
“…In the USA, one article identified high liability insurance premiums as a threat to viable smaller rural generalist practices, as well as limited technical facilities and the lack of an appropriate support workforce [ 78 ]. In Canada, difficult access to locums, the need for more education and training [ 79 ], low confidence in responding to paediatric emergencies and worsening physician shortages [ 80 ] are seen as the major barriers to developing the rural generalist workforce. In Europe, the pressures of providing the dual-role of primary care practitioner and specialist in rural communities [ 81 ], as well as an increasing centralisation of specialist services to larger centres, are negatively affecting RGM [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies also suggest that non-EM board-certified physicians themselves lack confidence is providing certain types of emergency care. 17 Further study is needed to quantify how variations in type and amount of PA supervision affect the quality and safety of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…EDs already use nurse practitioners and physician assistants for patient care, 5,19 as well as non-EM boardcertified physicians. 15,20 Physician shortages prompted the Association of American Medical Colleges in 2006 to set a goal of a 30% increase in enrollment in U.S. medical schools by 2015. 21 Identifying strategies to ensure adequate ED staffing is an important policy discussion.…”
Section: Discussionmentioning
confidence: 99%